Overcoming the Challenges of Commercializing Research’s Products :A Qualitative Research on the Experience of Higher Education in Indonesia - Carolina Magdalena Lasambouw; Ediana Sutjiredjeki; Neneng Nuryati (Soshum: Jurnal Sosial dan Humaniora, 2020)
The research products produced by tertiary institutions are intellectual property that benefits the community and provide an economic contribution. Even Universities are encouraged to increase their research products’ economic value because innovation considers successful when commercialized. Higher Education is direct to produce innovative products with high added value so that these products can be beneficial to the community and commercialized. However, not all innovation results are successful or can be commercialized, although, in principles, the commercialization of research products is no different from standard products’ commercialization. This paper outlines various efforts undertaken by universities/polytechnics in Indonesia to increase research output commercialization. The purpose of interviews is to determine how universities respond to the challenges of expanding the commercialization of their research output. The participants were the heads of research institutes and community service from twenty-one (21) tertiary institutions in Indonesia, consisting of nine (9) universities and twelve (12) polytechnics. The finding shows that only a few university and polytechnic have commercialized their research products; however, most higher education keeps doing their best to increase their capability to commercialize their research products. This study’s two implications are: 1) researchers need to involve “user” needs before developing a research proposal. 2) Management at the university needs to facilitate the commercialization of the academicians’ research products.